PERAN KOMPETENSI GURU DALAM MENGEVALUASI TUGAS YANG DIBERIKAN MELALUI PEMBELAJARAN ONLINE DI SMP NEGERI 1 KUANTAN HILIR SEBERANG - Masyhur; Fendri; Haprianti, Elvi; Putri, Meilizah (PGRI Provinsi Riau, 2021)
The Covid-19 pandemic requires teachers to continue to monitor and evaluate student competencies. This study aims to see how the competence of teachers is able to evaluate the tasks given in online or online-based learning by teachers of Junior High School 1 Kuantan Hilir Seberang. With the implementation of online learning, of course, there will be different treatments carried out by teachers in evaluating student performance to ensure that students can understand the material well. This study uses a descriptive method with data collection techniques by observation, interviews, and documentation. In Junior High School 1 Kuantan downstream across, the author looks at how teachers perform their role in evaluating student learning outcomes. Starting from giving assignments, assessing and then evaluating where the students' weaknesses lie, especially regarding understanding and attitudes. The teacher continuously evaluates student learning outcomes by paying close attention to student understanding. From the results of the research conducted, it was found that teacher competence was needed to find the weaknesses and obstacles experienced by students when the teacher gave assignments, especially learning assignments during the pandemic. Through this activity, weaknesses related to students' understanding and attitudes can be identified. Weaknesses in terms of understanding the material are corrected through giving material back via zoom/whatsapp video calls, while weaknesses in the attitude of not doing the job well are done through advice.